PENGARUH PENAMBAHAN LIMBAH PLASTIK JENIS POLYETHYLENE TEREPHTHALATE, LOW DENSITY POLYETHYLENE DAN POLYPROPYLENE TERHADAP NILAI KUAT TEKAN DAN DAYA SERAP AIR PAVING BLOCK - Dya Ayu Rahma Niar Rajab; Sahara Sahara; Ayusari Wahyuni (JFT : Jurnal Fisika dan Terapannya, 2021)
The use of plastic as an additional material in the manufacture of paving blocks is an alternative to reduce the accumulation of plastic waste. The purpose of this study is to determine the effect of adding plastic to the compressive strength and water absorption of paving blocks and to determine the composition that can produce optimal compressive strength and water absorption values. The design used in this study consisted of 3 treatments, namely normal paving blocks or without additional plastic, paving blocks with the addition of one type of plastic each, and paving blocks with the addition of three types of plastic at once. The amount of plastic used is 0.4% of the mass of paving blocks, with a ratio of cement and sand used, namely 1: 3. The tests carried out are compressive strength tests and water absorption tests. The test results show that the maximum compressive strength is found in the addition of three types of plastic waste, each 33.3% of the total fiber, which is 19.84 MPa with an increase of 17% from normal paving blocks. The sample also has the lowest absorption value of 4.1% with an increase of 14% from normal paving blocks. The value above can meet SNI 03-0691-1989 quality B, which means it can be used for parking lots